2022
DOI: 10.1039/d2ra03483b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a UiO-66/g-C3N4 composite using terephthalic acid obtained from waste plastic for the photocatalytic degradation of the chemical warfare agent simulant, methyl paraoxon

Abstract: UiO-66/g-C3N4 with a high surface area (1440 m2 g−1) and a high capillary volume (1.49 cm3 g−1) exhibited highly efficient degradation of dimethyl 4-nitrophenyl phosphate with t1/2 = 2.17 min.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…[ 18 ] The bands at 562 cm ‐1 and 468 cm ‐1 are assigned to the Cu−O stretches oscillations. [ 19 ] The bands at 850‐1000 cm ‐1 which attributed to the vibration of C‐H groups. [ 19 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 18 ] The bands at 562 cm ‐1 and 468 cm ‐1 are assigned to the Cu−O stretches oscillations. [ 19 ] The bands at 850‐1000 cm ‐1 which attributed to the vibration of C‐H groups. [ 19 ]…”
Section: Resultsmentioning
confidence: 99%
“…Polyethylene terephthalate (PET), ethylene glycol (EG, 99%), sodium hydroxide (NaOH, 98%), sulfuric acid (H 2 SO 4 , 98%), chromium(III) nitrate nonahydrate (Cr(NO 3 ) 3 .9H 2 O, 99%), hydrofluoric acid (HF, 48%), ethanol (C 2 H 5 OH, 99%), dimethylformamide (DMF, 98%), copper(I) iodide, sodium dodecyl sulfate (C 12 H 25 O 4 S), thioacetamide (CH 3 CSNH 2 , 98%), indium(III) chloride (InCl 3 , 98%), hydrochloric acid (HCl, 37%), 1,4-benzoquinon (BQ, 99%), tert-butyl alcohol (TBA, 99%). TPA was recovered from polyethylene terephthalate (PET) according to our previous study [24,25]. Chemicals in the work were purchased by Sigma-Aldrich and used without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…To solve this issue, researchers have investigated the use of recycled TPA produced from waste polyethylene terephthalate (PET) for MOF production [21][22][23][24]. Several studies have reported the successful synthesis of MOFs using recycled TPA [25,26]. Lo et al [27] described the facile and scalable production of nanoporous MOFs from PET waste.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Various semiconductor materials such as ZnO, AgBr, Fe 2 O 3 , g-C 3 N 4 , AgBr and TiO 2 have been utilized as photocatalysts. 10,11 Among these, ZnO is a promising candidate due to its superior oxidation resistance, stability, low cost, and non-toxicity, causing no secondary pollution. 12,13 However, the high band gap energy of ZnO (3.3 eV) leads to rapid recombination between holes (h + ) and electrons (e − ) resulting in reduced photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%